Epidemiology, thrombolytic management, and outcomes of acute stroke among patients with chronic kidney disease: a systematic review and meta-analysis. Issue 7 (8th June 2021) - Zamberg, Ido; Assouline-Reinmann, Marie; Carrera, Emmanuel; Sood, Manish M; Sozio, Stephen M; Martin, Pierre-Yves; Mavrakanas, Thomas A
Abstract: Background: The relative frequency of ischaemic versus haemorrhagic stroke among patients with chronic kidney disease (CKD) has not been clearly described. Moreover, no recent meta-analysis has investigated the outcomes of patients with CKD treated with thrombolysis for acute ischaemic stroke. We conducted a systematic review and meta-analysis to estimate the proportion of stroke subtypes and the outcomes of thrombolysis in CKD. Methods: A PubMed, EMBASE and Cochrane literature research was conducted. The primary outcome was the proportion and incidence of ischaemic versus haemorrhagic strokes among patients with CKD. In addition, we assessed the impact of CKD on disability, mortality and bleeding among patients with acute ischaemic stroke treated with thrombolysis. The pooled proportion and the risk ratio were estimated using a random-effects model. Results: Thirty-nine observational studies were included: 22 on the epidemiology of stroke types and 17 on the outcomes of thrombolysis in this population. In the main analysis (>99 281 patients), ischaemic stroke was more frequent than haemorrhagic among patients with CKD [78.3%, 95% confidence interval (CI) 73.3–82.5%]. However, among patients with kidney failure, the proportion of ischaemic stroke decreased and was closer to that of haemorrhagic stroke (59.8%, 95% CI 49.4–69.4%). CKD was associated with worse clinical outcomes in patients with acute ischaemic stroke compared with patients with preserved kidney function. Conclusions: The relative frequency of haemorrhagic stroke seems to increase as kidney function declines. Among patients with acute ischaemic stroke treated with thrombolysis, presence of CKD is associated with higher disability, mortality and bleeding, compared with patients with preserved kidney function. Graphical Abstract: